Implementation of the Independent Learning-Independent Campus Program at Cahaya Prima Bone University - Haedar Akib; Andi Fitiah; Isgunandar Isgunandar (Asha Publishing, 2025)
This study seeks to assess the execution of the Independent Learning-Independent Campus (MBKM) program at Universitas Cahaya Prima (UNCAPI) Bone and to identify the facilitating and obstructive elements affecting its implementation at UNCAPI Bone. The research employs qualitative methods, utilizing data collection approaches such as observation, interviews, and documentation. This study involved seven informants. The findings of this study indicate that the execution of the MBKM program at UNCAPI Bone, assessed through the indicators of communication, resources, disposition, and bureaucratic structure, has been conducted